A Data Envelopment-Based Clustering Approach for Public Sugar Factories in Privatizing Process. (10th August 2011) - Demirtas, Ezgi A.
Abstract : Turkish Sugar Inc., a public enterprise including 25 factories, is the first corporation of Turkish industry. According to the government policy, public sugar factories (PSFs) will be privatized as geography-based 6 portfolio groups in two years. As performance measures of PSF affect government, sugar producers, and several unions in privatizing process, a systematic approach is necessary to measure efficiencies and grouping factories. This paper uses a new DEA- (Data Envelopment Analysis-) based clustering approach for measuring efficiency scores of PSF and grouping them instead of geography- based portfolio groups. This new approach can help decision makers in privatizing process. At the same time, target values obtained by dual model can be used to eliminate inefficiencies of some PSFs.